Pendampingan Sertifikasi Halal UMKM di Kelurahan Karang Pule Mataram - Rahima, Phyta; Suriyati, Suriyati; Soraya, Siti; Rismayati, Ria (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2026)
Products with a halal certification label provide consumers with confidence as a form of protection, information on the product's halal status, and an ethical instrument in business. Good business actors with a sense of responsibility strive to obtain halal certification for the products they offer. The purpose of this community service is to provide assistance to MSMEs, such as food stalls or home-based businesses selling lalapan (Bale Lalapan), which have been established for approximately 8 months and do not yet have halal certification, to be directed in obtaining halal certification. The methods used in this community service activity include counseling, assistance, and explanations from the Certification Team to Business Owners facilitated by the Community Service team. The final result of the Community Service activities carried out by the Bumigora team is the issuance of halal certification from the Halal Product Guarantee Organizing Agency. With the issuance of Halal Certification to Bale Lalapan MSMEs, it is hoped that it will be able to increase income while increasing market reach. It is also hoped that Business Owners can understand the benefits of halal labeling of a product and understand the production process that is made according to halal standards with existing provisions, as well as being able to be applied in other business activities so as to be able to increase sales reach to larger institutions and become a motivation for other MSMEs in marketing their products.